1 Alternative heifer development systems utilizing corn residue and cover crops. (30th November 2020) - Speer, Hannah; Riley, Hannah; Cushman, Robert; Freetly, Harvey; Drewnoski, Mary
Abstract: Spring-born heifers (n = 1, 012) weaned at 148 ± 17 d were used in a 3-yr study to evaluate performance in winter development systems which utilized cover crop and corn residue grazing. Heifers were assigned to 1 of 3 treatments: grazing corn residue with dried distillers grains (CD) or wheat midds (CW) supplementation, or grazing late summer planted oat-brassica cover crop followed by corn residue supplemented dried distillers grains (CC). Grazing of corn residue (CD and CW) and cover crop (CC) began in early November. Supplementation during the corn residue phase was adjusted to target 55% of mature BW (338 kg) at breeding. After 63 d, CC were moved to corn residue; on d 77 CD and CW began receiving grower ration. In mid-February (d 98), heifers were comingled and managed in a single group. Breeding season began in June and lasted for 29 d. Prior to corn residue grazing, ADG of CC was greater (0.76 kg/d; P< 0.01) than CD or CW (0.58 kg/d and 0.49 kg/d, respectively). Gain during the last 35 d of the winter period for CC was 0.13 kg/d less than CW (P< 0.01) but not different from CD. Overall winter ADG was greater (P< 0.05) for CC (0.62 kg/d) than CD (0.53 kg/d) or CW (0.50 kg/d). Percent of mature BW prior to breeding was 52% for CC and 50% for CD and CW. May reproductive tract scores did not differ (P=0.26) between CC and CW but were greater (P< 0.05) in CC than CD. Pregnancy rates were affected by treatment (P< 0.01), with CC (76%) being greater than CD (68%) and CW (64%). Utilizing oat-brassica cover crops early in the winter followed by a lower rate of gain while grazing corn residue appear to be effective for developing beef heifers. USDA is an equal opportunity employer and provider.